Comparative study on AC susceptibility of YBa2Cu3O7−δ added with BaZrO3 nanoparticles prepared via solid-state and co-precipitation method - Mohd Hapipi, Nurhidayah; Lim, Jee Khan; Chen, Soo Kien; Lee, Oon Jew; Shaari, Abdul Halim; Awang Kechik, Mohd Mustafa; Lim, Kean Pah; Tan, Kar Ban; Murakami, Masato; Miryala, Muralidhar (MDPI, 2019)
Polycrystalline samples of YBa2Cu3O7−δ (Y-123) added with x mol% of BaZrO3 (BZO) nanoparticles (x = 0.0, 2.0, 5.0, and 7.0) were synthesized using co-precipitation (COP) and solid-state (SS) method. X-ray diffraction (XRD) patterns showed the formation of Y-123 and Y-211 as the major and minor phases, respectively. The samples prepared using COP method showed higher weight percentage of Y-123 phase (≤98%) compared to the SS samples (≤93%). A peak corresponding to BZO was also found in the samples added with BZO nanoparticles. The increasing intensity of the BZO peak as the BZO amount increased showed the increasing amount of the unreacted nanoparticles in the samples. Refinement of unit cell lattice parameters indicated that all the samples have an orthorhombic crystal structure and there is no orthorhombic-tetragonal phase transformation. As observed using scanning electron microscopy (SEM), all the samples showed randomly distributed grains with irregular shape. The average grain size for the pure sample prepared using COP method is smaller (0.30 µm) compared with that of the pure SS sample (1.24 µm). Addition of 7.0 mol% BZO led to an increase of average grain size to 0.50 μm and 2.71 μm for the COP and SS samples, respectively, indicating grain growth. AC susceptibility (ACS) measurement showed a decrease in the onset critical temperature, Tc-onset with BZO addition. Comparatively, Tc-onset for the COP samples is higher than that of the SS samples. The value of Josephson’s current, Io increased up to 2.0 mol% BZO addition, above which the Io decreased more drastically for the SS samples. The value of Io is 53.95 μA and 32.08 μA for the 2.0 mol% BZO added SS and COP samples, respectively. The decrease of Io is attributed to the distribution of BZO particles at the grain boundaries as also reflected in the drastic decrease of phase lock-in temperature, Tcj. As a result of smaller average grain size, the presence of more grain boundaries containing insulating BZO particles led to lower Io in the COP samples.